The nanostructure study on the mechanism of lime stabilize soil - Kassim, Khairul Anuar (Faculty of Civil Engineering, 2009)
The poor engineering properties of clayey soils can be altered through chemical stabilization, resulting in a material suitable for construction purposes. The effect of calcium-based stabilizers on the geotechnical properties of soils has been reported by many researchers. However, the amount of literature available on the micro-structural, molecular, and leaching characteristics of lime and in particular phosphoric acid stabilized soils has been rather limited. In this thesis, two soil types comprised mainly of montmorillonite and kaolinite minerals (i.e., Green Bentonite and White Kaolin) and two tropical soils (Laterite Clay and Pink Soil) were chosen. The primary objective of this investigation was to elucidate the possible mechanisms by which different soils are modified in a highly acidic and basic environment. This was achieved by studying the changes induced in soil-stabilizer matrix using X-ray Diffractometry (XRD), Energy Dispersive X-ray Spectrometry (EDAX), Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance spectroscopy (NMR), Cation Exchange Capacity (CEC) and BET surface area analysis. Also, in order to correlate the structural evolution of reaction products with pore water chemistry, leaching was performed on cured samples. This highlighted a very important point regarding the chemical composition of reaction products. The fact that in an acidic and basic environment (low and high pH), clay alumina was more liable to dissolution and dominant in the pore water chemistry. Therefore, it was rational to suggest that in lime and phosphoric acid treated samples, aluminate hydrate compounds were more likely to be formed. Also it was found that in lime treated Green Bentonite and Laterite Clay samples, the 2:1 layer structure of montmorillonite mineral and the coating action of free oxides on the surface of soil particles imposed inhibitive effects on the dissolution of clay alumina, respectively. Furthermore, it was found that the action of stabilizers was mainly surface associated and that they were unable to penetrate deeply through the crystalline clay structure. Finally, from engineering point of view, in comparison to acid stabilization, the lime treated samples exhibited much higher strength gains for all curing periods. Nevertheless, for Laterite Clay design mixes, the acid treated samples showed the most promising results with an almost threefold increase in the compressive strength of the natural soil over an 8 months curing period. The latter indicated that phosphoric acid can be used in a wisely manner as an alternative to alkaline stabilizers for treating acidic lateritic soils without having to remove the weak soil and replacing it with a superior material.